2010
DOI: 10.1016/j.str.2010.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Roles and the Movement of Hydrogen during Reaction Catalyzed by D-Xylose Isomerase: A Joint X-Ray and Neutron Diffraction Study

Abstract: SUMMARY Conversion of aldo to keto sugars by the metalloenzyme d-xylose isomerase (XI) is a multi-step reaction involving hydrogen transfer. We have determined the structure of this enzyme by neutron diffraction in order to locate H atoms (or their isotope D). Two studies are presented, one of XI containing cadmium and cyclic d-glucose (before sugar ring opening has occurred), and the other containing nickel and linear d-glucose (after ring opening has occurred but before isomerization). Previously we reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
166
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(183 citation statements)
references
References 48 publications
6
166
1
1
Order By: Relevance
“…Ring opening step. The initial step in the enzymatic isomerization of glucose to fructose involves the ring opening of a glucose molecule at M1 (12). To determine if a similar pathway is followed by Sn-Beta, the adsorption of 13 C labeled glucose and fructose into Sn-Beta and Si-Beta (pure-silica zeolite without Lewis acid active sites: used as control) was investigated using 13 C NMR (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ring opening step. The initial step in the enzymatic isomerization of glucose to fructose involves the ring opening of a glucose molecule at M1 (12). To determine if a similar pathway is followed by Sn-Beta, the adsorption of 13 C labeled glucose and fructose into Sn-Beta and Si-Beta (pure-silica zeolite without Lewis acid active sites: used as control) was investigated using 13 C NMR (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The preferred metal ions are Mg 2þ or Mn 2þ . Only recently, complementary X-ray and neutron diffraction techniques aimed at probing the location and dynamics of H/D atoms in XI crystal structures have been exploited to reveal important details of the enzyme reaction mechanism (12). Three important new features were elucidated: (i) the primary role of M1 (in conjunction with specific amino acid residues) is to destabilize the pyranose structure and promote the ring opening of the sugar, (ii) M2 binds and stabilizes O1 and O2 on the acyclic sugar, promoting the hydride shift from C2 to C1, and (iii) a hydroxyl group bound to M2 is responsible for the deprotonation/protonation sequences that shuttle protons involved in the interconversion of aldehydes and hydroxyl groups between O2 and O1.…”
mentioning
confidence: 99%
“…Our current mechanism of protonation of the O5 atom is consistent with the ring opening of another sugar, D-xylose, by its isomerase (50). Kovalevsky et al (50) showed that this reaction was driven by a basic amino acid (histidine or lysine), which provided a proton to O5 of D-xylose as a key step for the ring-opening reaction.…”
Section: Comparison Of Our Results With Previousmentioning
confidence: 99%
“…The accurate placement and orientation of amino-acid side chains and solvent molecules can result in a detailed understanding of the hydrogen bonding, via the deuterium patterns, which can facilitate the elucidation of catalytic mechanisms (Kossiakoff & Spencer, 1981;Niimura et al, 1997;Bennett et al, 2006;Blakeley et al, 2008;Coates et al, 2008;Blum et al, 2009;Adachi et al, 2009;Yagi et al, 2009;Tomanicek et al, 2010;Fisher et al, 2010;Kovalevsky et al, 2010).…”
Section: Introductionmentioning
confidence: 99%